The Association between High Fat Diet around Gestation and Metabolic Syndrome-related Phenotypes in Rats: A Systematic Review and Meta-Analysis - Mariana L. Tellechea (Nature Portfolio, 2017)
Abstract Numerous rodent studies have evaluated the effects of a maternal high-fat diet (HFD) on later in life susceptibility to Metabolic Syndrome (MetS) with varying results. Our aim was to quantitatively synthesize the available data on effects of maternal HFD around gestation on offspring’s body mass, body fat, plasma leptin, glucose, insulin, lipids and systolic blood pressure (SBP). Literature was screened and summary estimates of the effect of maternal HFD on outcomes were calculated by using fixed- or random-effects models. 362 effect sizes from 68 studies together with relevant moderators were collected. We found that maternal HFD is statistically associated with higher body fat, body weight, leptin, glucose, insulin and triglycerides levels, together with increased SBP in offspring later in life. Our analysis also revealed non-significant overall effect on offspring’s HDL-cholesterol. A main source of variation among studies emerged from rat strain and lard-based diet type. Strain and sex -specific effects on particular data subsets were detected. Recommendations are suggested for future research in the field of developmental programming of the MetS. Despite significant heterogeneity, our meta-analysis confirms that maternal HFD had long-term metabolic effects in offspring.